2009
DOI: 10.1002/jor.21009
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen upregulates expressions of matrix metalloproteinase-1, -8, -9, and -13 without affecting expressions of types I and III collagen in tendon cells

Abstract: Nonsteroidal antiinflammatory drugs are widely used to treat sports-related tendon injuries or tendinopathy. This study was designed to investigate the effect of ibuprofen on expressions of types I and III collagen, as well as collagen-degrading enzymes including matrix metalloproteinase (MMP)-1, -2, -8, -9, and -13. Rat Achilles tendon cells were treated with ibuprofen and then underwent MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. Reverse transcription-polymerase chain reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 33 publications
3
38
0
1
Order By: Relevance
“…This could suggest either that structural reorganization of the healing tendon is altered due to early ibuprofen administration or that earlier matrix degradation and production are altered by ibuprofen administration. NSAIDs have been shown to alter both cell motility and tenocyte matrix metalloproteinase expression in vitro [30,31], lending support to these ideas. Interestingly, the delayed group did exhibit a recovery of fiber alignment with increased postsurgery time, but this process seemed delayed as there was no significant difference between 1 and 2 weeks postsurgery, as in the control.…”
Section: Discussionmentioning
confidence: 75%
“…This could suggest either that structural reorganization of the healing tendon is altered due to early ibuprofen administration or that earlier matrix degradation and production are altered by ibuprofen administration. NSAIDs have been shown to alter both cell motility and tenocyte matrix metalloproteinase expression in vitro [30,31], lending support to these ideas. Interestingly, the delayed group did exhibit a recovery of fiber alignment with increased postsurgery time, but this process seemed delayed as there was no significant difference between 1 and 2 weeks postsurgery, as in the control.…”
Section: Discussionmentioning
confidence: 75%
“…For what concern corticosteroids injections there are several case reports [90,91] of tendon rupture after their use in patients while animal studies have shown that they lead to a reduction in tendon strength [92] , but these findings are not universal and there is a lack of goodquality research data to support their use in tendinopathy [93] . Nonsteroidal anti-inflammatory drugs (NSAIDs) are shown to modulate tendon cell proliferation, the expression of extracellular matrix components and degenerative enzymes [94,95] . As their use is common for sport-related symptoms, it is possible that they contribute to the development of tendinopathy [96] .…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
“…2 Non-steroidal anti-inflammatory drugs (NSAIDs) are widely prescribed and used to treat tendon injuries over the years. 5 However, these drugs usually treat only the symptoms of inflammation and not the disease cause. 4,6 Additionally, it has been observed several kinds of side effects related to long-term use of these drugs.…”
mentioning
confidence: 99%
“…1,9 Furthermore, very few is known about cellular changes related to this increased risk, 1 but it has been hypothesized that some pharmacological treatments are harmful to tendon due to up-regulate expressions of matrix metalloproteinases (MMPs) such as MMP-9 and MMP-13. 5 MMPs play an important role in tendon matrix morphology, it degrades collagen and proteoglycans in healthy and sickness conditions. 10 The tendon matrix remodeling is related directly to balance between MMPs and their inhibitors.…”
mentioning
confidence: 99%